Cyberhate: A review and content analysis of intervention strategies - Blaya, Catherine (Aggression and violent behavior, 2019)
This paper presents a review of intervention programmes against cyberhate. Over the last decade, the preoccupation over the use of electronic means of communication as a tool to convey hate, racist and xenophobic contents rose tremendously. NGOs, legal professionals, private companies, and civil society have developed interventions but little is known about their impact. For this review we followed the method and protocol from the guidelines from the Cochrane Collaboration Handbook for Systematic Reviews and the Campbell Collaboration Crime and Justice guidelines. The review identified three key intervention areas: law, technology and education through the empowerment of the individuals under the form of counter-speech. No specific intervention towards aggressors was found and most projects focus on prevention or victims through confidence building and skills learning to speak out, report and potentially react in an appropriate way. We did not find any rigorously assessed interventions, which highlights a gap in research and stresses the need for this type of studies. The evaluation of effectiveness of interventions needs to be included in the near future research agenda. Up to now, although intentions are good, we have no evidence that the steps that are undertaken are effective in preventing and reducing cyberhate. •Cyberhate has got negative consequences on individuals, communities and social cohesion.•Intervention schemes are designed to prevent and reduce hate online.•Interventions focus on three different areas: technological, legal, and internet literacy and counter speech.•There is no rigorous evaluation and a lack of evidence for effectiveness•Findings highlight the need for developping evaluations and inform public policies.•This study has implications for policy and practice. Findings can be used to design and implement effective programs against cyberbullying